Islandshästar med hosta och/eller prestationsnedsättning - Larsson, Kristin (2005)
The purpose of the study was to investigate whether or not Icelandic horses are less severely affected in clinical symptoms of cough or decreased performance than other breeds of horses. A breed variation in chronic respiratory disease severity was suspected based on clinical experience at the Institution for surgery & medicine, large animal, SLU Uppsala. A retrospective journal study of 17 Icelandic horses and 17 Swedish Standardbred horses with chronic problems with cough and/or decreased performance compared several measurements of disease severity.